Binocular Astronomy - Tonkin, Stephen (The Patrick Moore Practical Astronomy Series,, 2007)
Anyone who has used a binocular telescope or even wide-field binoculars to look at the night sky will know just how breathtakingly beautiful the view can be when you observe with both eyes. Observing galaxies and nebulae with 'regular' prismatic binoculars is just a beginning. Binocular eyepieces and adapters can be added to almost any commercially-made astronomical telescope, and of course specialized astronomical binoculars can be assembled or purchased complete. These range from modest instruments to giants that are basically two large telescopes mounted together. Binocular Astronomy contains everything you'll need to know about this exciting branch of astronomical observing. Understanding the physics and physiology of binocular visual astronomy is followed by an in-depth description of how to choose, test, and buy the best equipment. Details of care and maintenance, mounting, and using binocular telescopes follow. Finally, Steve Tonkin presents introductory lists of some of the most exciting objects for 2-inch (50mm) and 4-inch (100mm) binoculars, complete with finder charts. Begin your own journey into binocular astronomy here!